Glycolate catabolic bypass pathway integration in rice could be effective in lowering photorespiratory rate with modulating starch content and grain quality - Nayak, Lopamudra; Panda, Darshan; Dash, Goutam Kumar; Lal, Milan Kumar; Swain, Padmini; Baig, MJ; Kumar, Awadhesh (ORYZA-An International Journal of Rice, 2022)
Photorespiration, which is prevalent under higher temperature and arid conditions, significantly affects crop productivity by reducing yields up to 50% in C3 crops like rice under severe stress conditions. This is primarily attributed to a reduction in net photosynthetic rate (PN). Rice flag leaf photosynthesis is the primary supplier of sugar to the maturing spikelets after anthesis. This study evaluated the grain quality traits and starch content of the wild type (WT) and transgenic rice generated by introducing Escherichia coli (E. coli) glycolate catabolic pathway bypassed (GCPB) through agrobacterium mediated transformation. Leaf soluble protein, photosynthetic CO2 assimilation rate, leaf non-structural carbohydrate content, grain quality traits such as hulling and milling percentages, head rice recovery, water uptake, volume expansion, alkali spreading value, gel consistency, grain breadth, grain starch content and amylose content were affected to a great extent in GCPB transgenic plants (T4). This study indicates the possible role of photorespiratory bypass mechanism in the regulation of source-sink communication, starch biosynthesis and grain quality in rice.